The Role of Tumor Necrosis Factor (TNF) Alpha with Visual Field Defects in Primary Open Angle Glaucoma (POAG): Oral Presentation - Observational Study - Resident - Hutabarat, Muhammad Hendy Hasudungan; Sari, Masitha Dewi (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlaucoma is a group of progressive optic neuropathy disease characterized by degeneration ofretinal ganglion cells. This causes changes in the optic nerve and loss of visual field. Several studieshave revealed that there is a role for TNF Alpha in glaucoma cases. To determine the role TumorNecrosis Factor (TNF) Alpha Levels between visual field defects in Primary Open-angle Glaucomapatients. MethodsThis study is Observational Analytical with cross sectional data collection method. Examination ofthe field of view using the Humphrey visual field perimetry. ResultsThe sample of this research was 30 people with 16 (53.3%) male and 14 people (46.7%) female.Using the Spearman correlation test, it showed that there was no significant correlation betweenTNF alpha and field of view (p = 0.119). ConclusionTNF Alpha level was not significantly related to visual field defects.